Studies towards enantioselective metal-catalysed nucleophilic allylations using allenes - Di Sanza, Riccardo (2020)
The enantioselective intramolecular nickel-catalysed nucleophilic 1,2-allylation of ketones with (hetero)arylboronic acids or potassium vinyltrifluoroborate and progress towards the enantioselective intramolecular 1,4-allylation of enones with dialkylzinc nucleophiles are described. The first project is initiated by carbonickelation of allenes which gives the nucleophilic allylnickel species that cyclise by 1,2-allylation onto a tethered ketone to produce a range of chiral tertiaryalcohol containing aza- and carbocycles in excellent diastereo- and enantioselectivities. The second project is initiated by the oxidative cyclisation of Pd(0) with an allene tethered to an enone. The resulting palladacycle formed undergoes transmetalation with a dialkylzinc nucleophile, and subsequent reductive elimination affords 6,5-fused bicycles in high diastereoselectivity.